Synthesis and characterization of lanthanum cobaltite based cathode material for potential application in proton conducting fuel cell / Abdullah Abdul Samat - Abdul Samat, Abdullah (2014)
Proton conducting fuel cell (PCFC) is a device that converts chemical energy directly into electrical energy via electrochemical processes. Currently, one of the targets to boost the commercialization of this device is by lowering the current high operating temperatures (800 - 1000 °C) to intermediate temperatures (IT) (500 - 800 °C). However, at reduced temperatures, the device has performed a high interfacial polarization resistance (Rp) at cathode|electrolyte interface. In this work, strontiumdoped lanthanum cobaltite, Lao.6Sro.4Co03.5 (LSC064) was chosen as cathode material as it has shown a good performance at IT. The LSC064 powder was synthesized via polymeric complexing method using metal nitrate salts as precursor material. The calcined LSC064 powder was transformed to cathode slurries which have been prepared using four different electrode binders namely ethyl cellulose (EC), polyvinyl alcohol (PVA), polyvinyl butyral (PVB) and polyvinyl pyrrolidone (PVP). These slurries were separately painted on pellet surfaces of yttrium-doped barium cerate-zirconate, BaCe0.54Zr0.36Y0.1O2.95 (BCZY64) electrolyte to produce half-cell of LSC064|BCZY64|LSC064. The obtained powders and fabricated half-cells were respectively characterized by employing Thermogravimetric Analysis (TGA), Fourier Transform Infrared (FTIR) Spectroscopy, X-ray Diffractometry (XRD), Scanning Electron Micrsocopy/Electron Dispersive X-ray Spectrometry (SEM/EDS) and Electrochemical Impedance Spectroscopy (EIS). The»TGA results showed the lowest total weight loss, WTL (~86%) and the lowest thermal decomposition temperature, Tta (600 °C) were recorded at heating rates of 5 °C min"1 and 2 °C min"1 , accordingly. The XRD and SEM analysis revealed that a single perovskite phase of LSC064 with small particle size (~130 - 260 nm), respectively was obtained at calcination temperature of 800 °C with heating/cooling rate of 5 °C min"1 . The presence or absence of carbonyl compounds at ~1600 cm"1 and -860 cm"1 and metal-oxide (M-O) bond at 700 - 400 cm"1 after heat treatment was proven by the FTIR. SEM micrographs at cross-sectional view of the prepared cells with different electrode binders showed there were three areas corresponding to the LSC064, BCZY64 and LSC064|BCZY64 interface with or without crack and/or hole. Among all the electrode binders, only PVP has aided to form a good contact between the LSC064 and BCZY64 with no formation of crack and/or hole at LSC064|BCZY64 interface region. The elemental atomic percentage of elements at the interface region of the cell prepared with the PVP such as lanthanum, La (3.16%), barium, Ba (9.52%) and cerium, Ce (6.02%) was detected by EDS. The EIS results showed the Rp values in terms of area specific resistance (ASR) decreased as temperatures increased from 400 °C to 800 °C. A relatively low Rp of 0.48 Q cm2 at 700 °C indicates that the LSC064 is a promising cathode material for the PCFC at intermediate temperatures.